2013
DOI: 10.1159/000355191
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi Anemia Founder Mutation in Macedonian Patients

Abstract: Background: Fanconi anemia (FA) is a rare autosomal recessive disorder clinically characterized by developmental abnormalities, progressive bone marrow failure (BMF) and profound cancer predisposition. Approximately 65% of all affected individuals have mutation in the FANCA (Fanconi anemia complementation group A) gene. The mutation spectrum of the FANCA gene is highly heterogeneous. FA-A is usually associated with private FANCA mutations in individual families. Methods: We describe 3 unrelated patients with F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Kalb and colleagues also found that some FANCD2 mutations are highly specific for the patients' origin, such as splice mutation in intron 21, c.1948-16 T>G which is strongly related to the Turkish origin (KALB et al, 2007). Association of specific mutations with the certain populations was also found in other FA genes (MADJUNKOVA et al, 2014;TIPPING et al, 2001). Variants in intron 3, c.206-246 delG and exon 26, c.2396 C>A, found in this study, were not previously reported, even though large-scale studies on FA-D2 patients from multiple populations have been performed, indicating their possible linkage to the Serbian population.…”
Section: Discussionmentioning
confidence: 93%
“…Kalb and colleagues also found that some FANCD2 mutations are highly specific for the patients' origin, such as splice mutation in intron 21, c.1948-16 T>G which is strongly related to the Turkish origin (KALB et al, 2007). Association of specific mutations with the certain populations was also found in other FA genes (MADJUNKOVA et al, 2014;TIPPING et al, 2001). Variants in intron 3, c.206-246 delG and exon 26, c.2396 C>A, found in this study, were not previously reported, even though large-scale studies on FA-D2 patients from multiple populations have been performed, indicating their possible linkage to the Serbian population.…”
Section: Discussionmentioning
confidence: 93%
“…Genomic DNA was obtained from peripheral blood of the probands and their parents. Due to a suspicion of FA, the patients were screened for the known Macedonian founder mutation, c.190–256_283+1680del2040dupC (exon 3 deletion) in the FANCA gene, as already described ( 6 ). This mutation was only detected in patient 1 and her mother in a heterozygous state.…”
Section: Case Presentationmentioning
confidence: 99%
“…Furthermore, mutations that recur in one ethnic population have also been described. Recently, we have shown that FANCA c.190–256_283+1680del2040dupC is a founder mutation in Macedonian FA patients of Gypsy-like ethnic origin ( 6 ).…”
mentioning
confidence: 99%
“…In the field of immunogenetics, a series of studies have been published in well-known journals (Petlichkovski et al, 2004(Petlichkovski et al, , 2011Petlickovski et al, 2005;Spiroski et al, 2013). The research studies published by the Research Center for Genetic Engineering and Biotechnology regarding the molecular diagnostics of many monogenetic diseases and chromosomal disorders are numerous, some describing unique genetic variants (Efremov, Dimovski, & Huisman, 1994;Efremov et al, 1988Efremov et al, , 1996Madjunkova, Kocheva, & Plaseska-Karanfilska, 2014; Dimovski AJ, A large beta-thalassemia deletion in a family of Indonesian-Malay descent., 1996; Plaseska et al, 1990).…”
Section: Education In Genetics-formal and Informalmentioning
confidence: 99%